Water quality and UK agriculture: challenges and opportunities - Holden, J.; Haygarth, P. M.; Dunn, N.; Harris, Jim A.; Harris, R. C.; Humble, A.; Jenkins, A.; MacDonald, J.; McGonigle, D. F.; Meacham, T.; Orr, H. G. (Wiley: 12 months, 2017)
There are high aspirations for environmental water quality targets in the UK, but requirements for significant growth in agricultural production to meet both food security objectives and provide viable livelihoods for farmers make these hard to achieve. Significant water quality challenges are related to nutrients, pesticides, pharmaceuticals, pathogens, sediments and habitat alteration. To facilitate the challenges posed, there is a need for predictive, spatially distributed models to be developed that encompass the key aspects of agriculture and water management in order to inform future policy and organizations with an interest in land management. Additionally, there needs to be recognition from policy makers that different solutions are needed in different agri-water systems and that it often takes many years or decades for policies to have a sustained water quality impact. Long-term support for research infrastructure and the scientific skills base is required to enable measurement and data analysis necessary to inform decision making. Farmers need clearly articulated information on the issues and potential solutions on which to make informed management decisions regarding water. There are existing solutions to some problems and this knowledge needs to be effectively disseminated with appropriate incentives for implementation to have maximum impact. Greater collaboration between researchers, industry, and policy makers, with the necessary framework to deliver effective joint working, is urgently needed. There is also a need for a wider societal understanding of the land–water system and the various ways in which society pays (and might pay in the future) for the real value of water.
Keywords: pollution; farming; policy; freshwater; groundwater; catchment management